2016
DOI: 10.7150/ijms.13680
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage Activation Syndrome-Associated Markers in Severe Dengue

Abstract: Hemophagocytosis, a phenomenon of which activated macrophages phagocytosed hematopoietic elements was reportedly observed in severe dengue patients. In the present study, we investigated whether markers of macrophage activation syndrome (MAS) can be used as differential diagnostic markers of severe dengue. Two hundred and eight confirmed dengue patients were recruited for the study. Sandwich ELISA was used to determine serum ferritin, soluble CD163 (sCD163), and soluble CD25 (sCD25) levels. The population of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 54 publications
(49 reference statements)
0
32
0
1
Order By: Relevance
“…3 E ). It has been previously reported that MX2 is one of only four IFN-induced genes induced in an IRF3 and IRF7 independent manner in DENV-infected mice (38) and that CD163 in macrophages and CD14 + CD16 + monocytes contributes to the pathogenesis of SD (39, 40). Given the small number of subjects analyzed in this study and the female predominance, the predictive power of these candidate biomarkers warrants further validation in larger cohorts with a balanced number of females and males.…”
Section: Discussionmentioning
confidence: 99%
“…3 E ). It has been previously reported that MX2 is one of only four IFN-induced genes induced in an IRF3 and IRF7 independent manner in DENV-infected mice (38) and that CD163 in macrophages and CD14 + CD16 + monocytes contributes to the pathogenesis of SD (39, 40). Given the small number of subjects analyzed in this study and the female predominance, the predictive power of these candidate biomarkers warrants further validation in larger cohorts with a balanced number of females and males.…”
Section: Discussionmentioning
confidence: 99%
“…3E). It has been previously reported that MX2 is one of only four interferon-induced genes induced in an IRF3 and IRF7 independent manner in DENV infected mice [38] , and that CD163 in macrophages and CD14+ CD16+ monocytes contributes to the pathogenesis of SD [39,40] . Given the small number of subjects analyzed in this study, the predictive power of these candidate biomarkers warrants further validation in larger cohorts.…”
Section: Discussionmentioning
confidence: 97%
“…To the best of our knowledge, only one instance of diagnosis of dengue in an individual with SLE has been reported; this person was treated as an outpatient , suggesting that she had only mild symptoms. Most reported individuals with both dengue and autoimmune disease apparently developed the autoimmune diseases after having a DENV infection .…”
Section: Discussionmentioning
confidence: 99%